The effects of chemotherapy-induced alopecia on cancer patients’ distress - Long, Phan Thien; Loan, Pham Thi Bich; Duc, Dang Hoang; Minh, Huynh The; Tue, Pham Tang Tri; Dung, Ho Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Background: Hair is a human characteristic, which has an important role in presenting the individual gender, race, nation, social interaction as well as mental and physical health status. Chemotherapy-induced alopecia (CIA), which has an incidence of 65%, is known to be one of the most psychological shocks among cancer patients. Chemotherapy-induced Alopecia Distress Scale (CADS) created by a group of Korean scientists is a new tool developed to evaluate alopecia’s effects on patients’ mentality. It is necessary to investigate the effects of alopecia on cancer patients and to understand the demands of patients in coping with CIA. However, to our knowledge, this is a topic that is still lacking objective and scientific evidence in Hue, Vietnam. Therefore, we conducted the study to describe the alopecia characteristics of patients treated with chemotherapy, and to identify the distress level of cancer patients using CADS and the preference of patients to deal with the alopecia. Methods: A cross-sectional study was conducted on 56 cancer patients undergoing chemotherapy at the Oncology department of Hue University of Medicine and Pharmacy Hospital from 01/12/2020 to 25/03/2021. The hair loss grade was assessed by CTCAE and the level of distress was evaluated by CADS. Statistical analysis was performed in Microsoft Excel 2016 and the R 3.6.0 program. Results: The mean age of patients in our study was 56.48 ± 10.244. Of all 56 patients, the majority of participants were female (69.6%), married (82.1%), and had above-average economic status (67.9%). Breast cancer patients accounted for the highest percentage with 39.3%. Most of the patients were in grade III (32.1%) and grade IV (39.3%). Our study revealed that 82.1% of patients having hair loss at grade 2 according to CTCAE 5.0. Evaluating by CADS showed that 87.5% of participants experienced low distress. Hat/ headscarf and wig were the most popular coping strategy against the CIA (66.1% and 35.7%, respectively). Scalp cooling is a new method that can prevent the CIA effectively. A proportion of 41.1% was willing to try the scalp cooling systems. Conclusions: Alopecia grade 2 accounted for the majority of patients in our study (82.1%). This was a symptom that should be concerned, however, our study revealed that the alopecia’s effects were not so serious among patients in the study. Most of the patients did not worry about chemotherapy - induced alopecia (89.3%), and 87.5% of participants experienced low distress, while there was still a proportion of 12.5% with higher distress. To cope against alopecia, many feasible coping strategies have been used by patients, including hat/ headscarf or wig.